A consumption model for measuring poverty: an exploratory exercise - Paim, Laily (Kluwer Academic Publishers, 1995)
The general purpose of this study was to develop and evaluate a consumption model to estimate poverty level of paddy farmers in Malaysia. The consumption model was based on four selected domains of life, namely quality of housing and local facilities, durable ownership, health status, and food intake. The data for this study were taken from the Level of Living Study (1986-1990) conducted by the Department of Human Development, Agriculture University of Malaysia. The sample consisted of 600 paddy farmers, selected randomly. Two consumption models - orthogonal and oblique - were tested using confirmatory factor analysis. The findings revealed that the oblique model was better fitted to the data than the orthogonal model.